Temperature-stable NdFeB micromagnets with high-energy density compatible with CMOS back end of line technology. Issue 3 (2016) - Reimer, Tim; Lofink, Fabian; Lisec, Thomas; Thede, Claas; Chemnitz, Steffen; Wagner, Bernhard
ABSTRACT: The performance of a novel type of NdFeB micromagnets fabricated by agglomeration of magnetic powder by atomic layer deposition is investigated. The ALD-bonded micromagnets can withstand standard BEOL (back-end of line) processing and heat treatments at temperatures of up to 400 °C in air and vacuum without any significant impact on the demagnetization curves. By optimized packing density a remanence of 660 mT is realized for the micromagnets. The coercivity µ0 Hc = 890 mT remains constant for all samples and corresponds to the powder value. A comparison of the demagnetizing behavior of micromagnets with theory of solid body magnets prove that the influence of particle shape and hollow spaces on demagnetizing field is low. Hence, a similar impact of shape on stray field and forces as for solid body magnets can be assumed when integrating NdFeB ALD-bonded micromagnets in applications.